Culturally mixed co-branding product framing in China: the role of cultural sensitivity, product quality, and purchase probability - Candy Lim Chiu; Han-Chiang Ho; Zhengqiao Xie; Qi Wu; Yuqi Yuan (Humanities & Social Sciences Communications, 2024)
Abstract Chinese consumers have shown a strong preference for foreign brands (FBs) for many years. However, in recent years, rising patriotism has spurred Chinese consumers to source locally, indicating a shift in preference for patriotic brands (PBs). FBs operating in the world’s second-largest market are now framing their marketing strategies to appeal more to Chinese consumers. This study examines two culturally mixed co-branded product (CMCP) framing strategies: foreign  ×  host culture (FB × PB) and host  ×  foreign culture (PB × FB). The results show that the effects of product fit and cultural congruence on co-branding attitude for PB × FB is stronger than that of FB × PB, and the influence of brand fit on co-branding attitude for FB × PB is stronger than that of PB × FB. Additionally, the impact of the co-branding attitude on cultural sensitivity was significant for PB × FB, whereas that on product quality was significant for FB  ×  PB. Furthermore, the effects of co-branding attitude on purchase probability were significant for both types of CMCP framing (FB × PB < PB × FB). Structural equation modeling was used to analyze the preferences of 479 Chinese consumers. This study provides significant recommendations for FBs and PBs to benefit from a strong wave of patriotism in China through culturally mixed framing and glocalization co-branding strategies.